2010
DOI: 10.1057/lst.2010.2
|View full text |Cite
|
Sign up to set email alerts
|

Latin American immigrants in Indianapolis: Perceptions of prejudice and discrimination

Abstract: !The article focuses on immigrants' interactions with the Indiana natives, with emphasis in the city of Indianapolis and its suburbs. More specifically, this study aims at providing an understanding of the experiences of Latin American immigrants with special attention to perceptions of prejudice and discrimination and to feelings of social exclusion. A substantial proportion of Latin American immigrants interviewed indicated that they considered Indiana natives to be prejudiced and that they had personally ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This finding is consistent with other studies which have identified language as a targeting mechanism for discrimination (Ayón & Becerra, 2013). When immigrants are unable to communicate in English, have limited English-speaking skills, or have a heavy accent, it is assumed that they are undocumented and that they will not take action on their behalf (Ayón & Becerra, 2013; Menendez Alarcón & Novak, 2010; Nier et al, 2012). Furthermore, discrimination based on language abilities was high across all profiles compared with other forms of discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with other studies which have identified language as a targeting mechanism for discrimination (Ayón & Becerra, 2013). When immigrants are unable to communicate in English, have limited English-speaking skills, or have a heavy accent, it is assumed that they are undocumented and that they will not take action on their behalf (Ayón & Becerra, 2013; Menendez Alarcón & Novak, 2010; Nier et al, 2012). Furthermore, discrimination based on language abilities was high across all profiles compared with other forms of discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…If additional patterns emerge, we hypothesize that these profiles will emphasize certain forms of discrimination over others. Previous research indicates that Latino immigrants report high levels of discrimination based on their English language abilities (Ayón & Becerra, 2013; Menendez Alarcón & Novak, 2010; Nier, Gaertner, Nier, & Dovidio, 2012) and as they interact with institutions (Guendelman, Angulo, Wier, & Oman, 2005); thus, differences in profiles may reflect these findings. Moreover, we hypothesize that protective factors will be associated with lower frequency discrimination profiles.…”
Section: Current Studymentioning
confidence: 99%
“…The discrimination factor includes 11 items. Similar to Córdova and Cervantes (2010), Cohen and Merino Chavez (2013), and Menéndez Alarcón and Novak (2010), the 11 items capture discrimination based on language, ethnicity, and intergroup discrimination. Additionally, questions reflect multiple venues where immigrants experience bias and prejudice such as the workplace, when accessing public services, and in public spaces like restaurants, stores, and parks.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly one third of Latinos report they, a family member, or close friend has been discriminated in the past 5 years due to their ethnicity (Lopez, Morin, & Taylor, 2010). Latino immigrants are subjected to racial profiling and discrimination when accessing public services (Ayón, 2014;Guendelman, Angulo, Wier, & Oman, 2005), in day-to-day interactions with mainstream society (Cohen & Merino Chavez, 2013;Menéndez Alarcón & Novak, 2010;Negi, 2013), and intragroup discrimination (Córdova & Cervantes, 2010). Assumptions are made about Latinos' legal status based on their appearance and language abilities (Ayón & Becerra, 2013;Menéndez Alarcón & Novak, 2010) with those who are dark skinned and who have limited English proficiency bearing most of the burden.…”
Section: Impact Of Immigration Policiesmentioning
confidence: 99%
“…While the word “new” dominates the scholarship of Latinos in non‐traditionally recognized destinations, it is important to remember that in many cases neither the immigrants themselves nor the towns they inhabit are necessarily new to the migrant stream. Moreover, many of the inquiries on “new” destinations focus on the non‐Latino response and issues of discrimination as a means of gauging the acceptance and social integration of Latinos in these areas (Fraga et al 2010; Marrow 2005; Grey and Woodrick 2005; Menéndez‐Alarcón and Novak 2010; Rich and Miranda 2005; Sanchez 2009). This non‐Latino reaction is critical for understanding what these Latino communities faced, but beyond the issues of reception or the absence of amenities lies the pivotal moments of Latinos enacting a sense of self in these “new” environments.…”
Section: Ethnic Belonging In “New” Communitiesmentioning
confidence: 99%